Chronological events in neonatal auditory screening - review - Munjal, Manish; Munjal, Vineeta; Bansal, Vasu; Munjal, Shubham (International Journal of Contemporary Pediatrics, 2020)
Neonatal screening for auditory impairment necessitates a meticulous and exhaustive work to detect at an early age this deficit and thereby plan an appropriate rehabilitative modality test, the speech maybe effected.